Machinery designing aided by augmented reality technology - Januszka, Marcin; Moczulski, Wojciech (Computer Assisted Methods in Engineering and Science, 2022)
This paper describes results of the research concerning an augmented reality (AR) system for CAD design, developed within the framework of MSc Thesis in the Department of Fundamentals of Machinery Design. The authors present advantages resulted from utilization of AR systems allowing to combine the interactive computer-generated world with an interactive real world in such a way that they appear as one environment, especially in CAD design. The authors decided to apply the system to aid the designer of the machinery systems by choosing standard parts. The system enables the user to easily view the 3D models of standard parts from any perspective, in more natural, intuitive way than traditional one (on the computer screen). Next, the user can export the model to the modeling software and use it to model some machinery system. This paper presents possibilities of using AR technology in CAD design with the hope that maybe someday it would become an integral part of a standard design process.